Gender differences in preferences for non-pecuniary benefits in the labor market: Experimental evidence from an online freelancing platform - Rakesh Banerjee; Tushar Bharati; Adnan M. S. Fakir; Yiwei Qian; Naveen Sunder (Asian Development Bank Institute (ADBI), 2023)
We conduct an experiment on a major international online freelancing labor market platform to study the impact of greater flexibility in choosing work hours within a day on female participation. We post identical job advertisements (for 320 jobs) covering a wide range of tasks (80 distinct tasks) that differ only in flexibility and the wage offered. Comparing the numbers of applicants for these jobs, we find that though both men and women prefer flexibility, the elasticity of response for women is twice that for the men. Flexible jobs receive 24 percent more female applications and 12 percent more male applications compared to inflexible jobs. Our findings have important implications for explaining gender differences in labor market outcomes and for firms interested in attracting more women employees.
Keywords: J22; O14; J16; L86; 330; workplace flexibility; online freelancing jobs; female labor force participation